Analisa Kepastian Hukum Pada Putusan Mahkamah Konstitusi Nomor 102/PUU-XVIII/2020 Tentang Uji Materil Pasal 12A Ayat 1 Undang-Undang Perbankan 1998 - Nasution, Indria Alamanda (Lisyabab : Jurnal Studi Islam dan Sosial, 2025)
This research discusses the Constitutional Court Decision No.102/PUU-XVIII/2020 which is the result of an application for the right to judicial review of Law no. 10 of 1998 on Banking regarding the 1945 Constitution. It contains the dynamics of differences in interpretation from the OJK and DJKN in interpreting article 12A paragraph 1 in the banking law. Then this research wants to explain the legal certainty that is represented by the request for the right to review which resulted in the Constitutional Court Decision. This research is qualitative research, which focuses on text analysis and library research literature. And the approach used is a normative juridical approach. The results of this research show that the legal uncertainty of article 12A paragraph 1 of Law No. 10 of 1998 concerning Banking can be seen from the differences in interpretation identified from three important problems based on legal interpretation issues, namely intent, vagueness and complexity. Then the Constitutional Court Decision No.102/PUU-XVIII/2020 adequately represents the role of judges in implementing a balance between justice, expediency and legal certainty